Evaluating Institutional Drivers of the Knowledge-Practice Gap: A Mixed-Methods Study on the Transition to Entrepreneurial Practice - Daniel Kurniawan; Damelina Basauli Tambunan (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Despite the increasing integration of entrepreneurship into business school curricula, a persistent "knowledge-practice gap" remains, where students struggle to translate theoretical literacy into real-world business execution. Drawing on Social Cognitive Career Theory (SCCT), this study evaluates the efficacy of the university ecosystem—comprising Entrepreneurial Culture, Teaching, and Education—in driving students through the developmental chain toward Entrepreneurial Practice. Utilizing a Mixed-Methods Explanatory Sequential Design, quantitative data was first collected from 139 business students and analyzed via Partial Least Squares Structural Equation Modeling (PLS-SEM) to test nine hypothesized paths. This was followed by qualitative Key Informant Interviews (KII) with seven selected participants to decode the "why" behind the statistical findings. The results reveal that while Entrepreneurial Teaching serves as a significant driver of both Mindset and Competence, the formal Curriculum (Education) and Institutional Culture often fail to directly stimulate the transition to practice. Qualitative findings suggest that this "structural disconnect" is fueled by pedagogical rigidity and perceived systemic barriers, such as financial constraints and a focus on academic compliance over market agility. The study concludes that for universities to move beyond "theoretical literacy," they must transition toward agile, practitioner-integrated models that foster individual agency and functional mastery. These findings provide a clear roadmap for educational leaders to bridge the knowledge-practice gap and equip the next generation of leaders with the practical skills needed for effective entrepreneurial leadership. Keywords: entrepreneurship education; entrepreneurship practice; knowledge-practice gap; mixed-method research; social cognitive career theory